Proceso de atención nutricional en paciente masculino de 54 años de edad con hipertrigliceridemia. - Cordero Camacho, Jefferson Joel (2022)
The present clinical case deals with a 54-year-old male patient with a family pathological history such as hypertriglyceridemia and diabetes, the first of these being the only one that presents as a personal pathological history. He is referred to the nutritionist by a general practitioner since the routine tests showed irregularities in the levels of triglycerides in plasma, reflected in the biochemical assessment, in which values outside the normal ranges are found, the same ones that confirm a diagnosis. Hypertriglyceridemia doctor. He has a weight of 89kg and a height of 170cm, in which, through anthropometric assessment, he has a Body Mass Index (BMI) of 30.79kg/m 2, which indicates that he is in a nutritional status of type I obesity, for which is carried out a dietary prescription appropriate to their nutritional requirements, the same as a Hypofat diet, divided into 5 meals a day, the same consisting of three main meals plus two snacks. A nutritional control will be carried out once a month after the second appointment, which will be 15 days after the first for better follow-up, until the patient is recovered, achieving a decrease in plasma triglyceride levels, along with the degree of obesity present.